Effects of Nitrogen and Sulfur Sprays on the Growth and Production of Broccoli Brassica Oleracea var. Italica L. - Mushtak F. Karomi Kisko; Nabil Jwad Kadhum; Zainab Anwar Ali; Noora Saheb Abid (مجلة بغداد للعلوم)
In order to achieve optimal plant growth and production, essential nutrients must be readily available in adequate quantities and in a balanced proportion to give a good yield, especially broccoli which has health benefits that may not be found in many other plants. For this purpose, this experiment was carried out during the seasons 2019/2020 in the botanical garden of the Department of Biology, College of Science for Women, University of Baghdad, to study the effects of nitrogen and sulphur and their interaction on eight parameters reflecting the overall traits of vegetative growth, yield, and chlorophyll content of broccoli Brassica oleracea L. (var. italic JASSMINE F1 Hybrid). A factorial design with three replicates was used, each with 7 plants treated via foliar spraying. The first factor included three groups; control N0 (distill water spray), N1 (500 mg.l-1 nitrogen), and N2 (1000 mg.l-1 nitrogen). The second factor also included three groups; control S0 (distill water spray), S1 (500 mg.l-1 sulfur), and S2 (1000 mg.l-1 sulfur). We used Urea (CO(NH2)2) as a nitrogen source and zinc sulphate (ZnSO4) as a sulfur source. As for the treatment with nitrogen, the results revealed that N2 treatment caused the significantly highest values in all the studied traits, except for the plant height, where there was no significant difference between N1 and N2. As related to the treatment with sulphur, the results showed that S2 treatment resulted in the significantly highest values of leave area, leave dry weight, and root fresh weight. S2 also caused the highest values, but with no significant differences, of plant height, stem diameter and chlorophyll content index. S1 treatment, on the other hand, caused insignificantly higher values of leave number per plant and main curd weight. Based on the results of the interaction between nitrogen and sulfur, S1N2 treatment resulted in the significantly highest values as compared to all other treatments of all the studied traits, except for the plant height, root fresh weight, and main curd weight. The results presented here may facilitate improvements of Broccoli cultivation with suitable nutrient concentrations for sustainable agriculture. In conclusion, the present study comes up with the following: nitrogen and sulfur and their interaction enhance significantly the growth and production of broccoli.